2015
DOI: 10.1007/s12038-015-9526-4
|View full text |Cite
|
Sign up to set email alerts
|

TORC2 and eisosomes are spatially interdependent, requiring optimal level of phosphatidylinositol 4, 5-bisphosphate for their integrity

Abstract: The elucidation of the organization and maintenance of the plasma membrane has been sought due to its numerous roles in cellular function. In the budding yeast Saccharomyces cerevisiae, a novel paradigm has begun to emerge in the understanding of the distribution of plasma membrane microdomains and how they are regulated. We aimed to investigate the dynamic interdependence between the protein complexes eisosome and TORC2, representing microdomains MCC and MCT, respectively. In this study, we reveal that the ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Moreover, it had been suggested that these two compartments are discrete (Berchtold and Walther 2009). However, as we found and document here, a substantial fraction of Avo2 is readily found in association with the diagnostic eisosome marker Pil1, in agreement with the observations of at least one other group (Bartlett et al 2015). Furthermore, there is convincing evidence that the Avo2-interacting proteins and eisosome components Slm1 and Slm2 are required for TORC2-mediated phosphorylation of Ypk1 (Berchtold et al 2012;Niles et al 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, it had been suggested that these two compartments are discrete (Berchtold and Walther 2009). However, as we found and document here, a substantial fraction of Avo2 is readily found in association with the diagnostic eisosome marker Pil1, in agreement with the observations of at least one other group (Bartlett et al 2015). Furthermore, there is convincing evidence that the Avo2-interacting proteins and eisosome components Slm1 and Slm2 are required for TORC2-mediated phosphorylation of Ypk1 (Berchtold et al 2012;Niles et al 2012).…”
Section: Discussionsupporting
confidence: 92%
“…Initially, it was reported that all of the components of TORC2, including Avo2, reside in a PM microdomain dubbed the "MCT" that is distinct from eisosomes (Berchtold and Walther 2009). However, subsequent work demonstrated that Avo2 partitions between TORC2 and eisosomes (Bartlett et al 2015). For these reasons, and having established that MAPK phosphorylation does not affect Avo2 stability ( Figs.…”
Section: Mapk Phosphorylation Of Avo2 Alters Its Subcellular Localizamentioning
confidence: 98%
“…Thus we investigated whether overproduction of elements of the TORC2 pathway (the Pkh2 kinase; TORC2 components Avo1, Avo2, Avo3 and Tor2; downstream AGC kinases Pkc1, Sch9 and Ypk1; and the Slm1 adaptor) led to effects similar to those caused by Akt. We also overproduced TORC2-signaling targets, like ceramide synthases Lac1 and Lag1 27 , and MCC/eisosome components Lsp1, Pil1 and Sur7 12 , because MCC/eisosomes are also related to PtdIns4,5P 2 regulation 11 , 48 . As shown in Table S1 and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the latest years, accumulated evidence indicates that the PM is organized in mosaic-like microdomains, the most prominent being the Membrane Compartment containing Pma1 (MCP), the Membrane Compartment containing Can1 (MCC; coincident with a furrow-like structure named eisosome), and the Membrane Compartment containing Tor2 (MCT) 7 , 8 , but there are probably less conspicuous PM microdomains 9 . MCP compartments have been reported to be active sites of endo- and exocytosis 10 , whereas the MCC and MCT are involved in PtdIns4,5P 2 homeostasis 11 . The invaginated PM furrows of MCCs are characteristically marked by BAR domain-containing proteins Pil1 and Lsp1 12 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…ATG1 is a downstream substrate of TOR, but evidence from Drosophila suggests ATG1 can also be an upstream regulator of TOR [ 48 ]. MDG1/YNL173C is also a component of the yeast eisosome [ 49 ], a membrane microdomain that interacts with TORC2 [ 50 ]. Although Abl1, according to PSORTII, is not predicted to be membrane localized, these potential links between MDG1/YNL173C and TOR in yeast might give tantalizing hints about how Abl1, and thus glucose, regulates TOR in M .…”
Section: Discussionmentioning
confidence: 99%